2020
DOI: 10.1002/jnr.24599
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic modulation of neuronal gap junction circuits in the CNS of the leech

Abstract: Gap junctions (GJs) are widely distributed in brains across the animal kingdom. To visualize the GJ-coupled networks of two major mechanosensory neurons in the ganglia of medicinal leeches, we injected these cells with the GJ-permeable tracer Neurobiotin. When diffusion time was limited to only 30 min, tracer coupling was highly variable for both cells, suggesting a possible modulation of GJ permeability. In invertebrates the innexins (homologs of vertebrate pannexins) form the GJs.Because extracellular adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 70 publications
(136 reference statements)
2
7
0
Order By: Relevance
“…In our dataset, the effect of the network on the T3 cell was clearly visible as postsynaptic potentials during the zero stimulation periods in the repeated control protocol ( Supplementary Figure 2 ). P cells also display neurobiotin coupling via gap junctions with several interneurons ( Segura et al, 2020 ), but we did not see any postsynaptic potentials in our P1 cell recordings. Rz cells are only coupled to their homolog Rz cell in the same ganglion ( Segura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In our dataset, the effect of the network on the T3 cell was clearly visible as postsynaptic potentials during the zero stimulation periods in the repeated control protocol ( Supplementary Figure 2 ). P cells also display neurobiotin coupling via gap junctions with several interneurons ( Segura et al, 2020 ), but we did not see any postsynaptic potentials in our P1 cell recordings. Rz cells are only coupled to their homolog Rz cell in the same ganglion ( Segura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 60%
“…P cells also display neurobiotin coupling via gap junctions with several interneurons ( Segura et al, 2020 ), but we did not see any postsynaptic potentials in our P1 cell recordings. Rz cells are only coupled to their homolog Rz cell in the same ganglion ( Segura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Gap junction permeable tracer injection into dorsal T cells revealed a highly variable number of electrically coupled neurons. This number depends on extracellular ATP, suggesting 10.3389/fncel.2023.1186997 modulation of network interactions (Segura et al, 2020). Hence, the modulation of gap junctions between pairs of T cells and other cell types probably contributes to the response variability between individual cells and maybe also over recording time.…”
Section: Effects Of Synaptic Inputsmentioning
confidence: 99%
“…Applying electrophysiological double recordings, dye injections for anatomical studies, and compartmental modeling, we investigate three potential factors for the observed response variability within and between T cell locations: (1) The time-dependent activity changes reported by Meiser et al (2019) and Scherer et al (2022) . (2) Synaptic input that the T cells receive from the unstimulated network ( Baylor and Nicholls, 1969b ; Scherer et al, 2022 ), and from a coupled T cell in the same ganglion ( Baylor and Nicholls, 1969b ; Meiser et al, 2019 ) (3) The anatomical structure ( Muller and McMahan, 1976 ; Segura et al, 2020 ), which we also compare to T1 cells. While all of them contribute to the variability within the T cells recorded at each of the soma locations, we rule out that any of these factors can exclusively explain the systematic difference in excitability between T2 and T3 cells.…”
Section: Introductionmentioning
confidence: 99%